The question is x^3 y^3 + 27.

Hi Melanie,

x^3y^3+27

=(xy+3)(x^2y^2-3xy+9).......................................using x^3+y^3=(x+y)(x^2-xy+y^2)

Meena

The question is x^3 y^3 + 27.

Tutors, please sign in to answer this question.

Strongsville, OH

Hi Melanie,

x^3y^3+27

=(xy+3)(x^2y^2-3xy+9).......................................using x^3+y^3=(x+y)(x^2-xy+y^2)

Meena

Wallingford, CT

This is in the form a^{3} + b^{3}, where a is xy and b is 3. The factoring formula is a^{3} + b^{3} = (a + b)*(a^{2} - ab + b^{2}).

x^{3}y^{3 }+27 = (xy)^{3 }+ 3^{3 }= (xy + 3)(x^{2}y^{2 }- 3xy + 9)

- Algebra 5068
- Algebra 1 4076
- Math 9883
- Factoring Polynomials 119
- Algebra 2 3504
- Factorization 22
- Factoring By Grouping 19
- Math Help 5453
- Quadratic Equations 530
- Polynomials 342